The Role of an Integrated Administration System in Reducing Patient Waiting Times in the Emergency Department at Grandmed Hospital Lubuk Pakam in 2025 - Rahmad Ramadhan Ritonga; Arif Sujatmiko; Putri Sari Maharani (JURNAL KESMAS DAN GIZI (JKG), 2025)
The Emergency Department (ED) is a vital hospital service that is required to provide fast, accurate, and efficient care. However, administrative processes that are not fully integrated often prolong patient waiting times. This study aims to analyze the role of integrated administrative systems in reducing patient waiting times at the ED of Grandmed Hospital Lubuk Pakam in 2025. A quantitative research design with a cross-sectional approach was applied, involving 100 patients and 20 administrative staff selected through purposive sampling. Data were collected through patient waiting time observations, staff perception questionnaires, and hospital documents. The results showed that most staff assessed the integrated administrative system as effective (75%). The average patient waiting time decreased from 7 minutes to 4 minutes after the system was implemented, meeting the Indonesian Ministry of Health’s service standard (≤5 minutes). Spearman correlation analysis revealed a significant relationship between administrative system effectiveness and patient waiting time (p = 0.002; r = –0.521). Simple linear regression further indicated that the effectiveness of the administrative system significantly contributed to reducing patient waiting times, with an effect size of 37% (R² = 0.37). In conclusion, the integrated administrative system plays an important role in improving the efficiency of ED services by reducing patient waiting times, and its continuous optimization is strongly recommended.